Survei Daya Tahan Kardiovaskular dan Daya Tahan Otot Lengan Atlet Arung Jeram Kabupaten Magelang Dalam Persiapan PORPROV 2023 - Shena Dioreski Arsenal; Sahri Sahri (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: The components of the physical condition of rafting sports that are most needed include cardiovascular endurance and arm muscle endurance. The aim of this study was to determine cardiovascular endurance in rafting athletes in Magelang Regency and to determine arm muscle endurance in rafting athletes in Magelang Regency in preparation for PORPROV 2023. Methods: This research is a quantitative descriptive study using survey methods. The research instrument uses MFT and Push Up test. The sample used was 22 athletes using a total sampling technique, namely rafting athletes from Magelang Regency who entered the PORPROV 2023 championship. Results: The results showed that of the 13 male athletes, 6 had good cardiovascular endurance, 3 moderate, 3 less, and 1 very poor. Meanwhile, out of 9 female athletes, 1 had very good cardiovascular endurance, 2 had good, 4 moderate, and 2 had poor. Of the 13 male athletes, 6 had good arm muscle endurance, 2 had moderate, 4 had less, and 1 had very little. Meanwhile, of the 9 female athletes, 3 had good arm muscle endurance, 3 moderate, and 3 lacked. Conclusions: The conclusion based on the results and discussion is that in general regarding cardiovascular endurance and muscle endurance in the male rafting athletes in Magelang Regency in preparation for PORPROV 2023 the highest frequency is in the good category, while in the female rafting athletes in Magelang Regency the highest frequency is in the moderate category. Methods: This research is a quantitative descriptive study using survey methods. The research instrument uses MFT and Push Up test. The sample used was 22 athletes using a total sampling technique, namely rafting athletes from Magelang Regency who entered the PORPROV 2023 championship. Results: The results showed that of the 13 male athletes, 6 had good cardiovascular endurance, 3 moderate, 3 less, and 1 very poor. Meanwhile, out of 9 female athletes, 1 had very good cardiovascular endurance, 2 had good, 4 moderate, and 2 had poor. Of the 13 male athletes, 6 had good arm muscle endurance, 2 had moderate, 4 had less, and 1 had very little. Meanwhile, of the 9 female athletes, 3 had good arm muscle endurance, 3 moderate, and 3 lacked. Conclusions: The conclusion based on the results and discussion is that in general regarding cardiovascular endurance and muscle endurance in the male rafting athletes in Magelang Regency in preparation for PORPROV 2023 the highest frequency is in the good category, while in the female rafting athletes in Magelang Regency, the highest frequency is in the moderate category.